Clinical significance and different strategies for re-elevation of plasma EBV-DNA during treatment in pediatric EBV-associated hemophagocytic lymphohistiocytosis - Wenzhi Zhang; Yun Peng; Yining Qiu; Li Cheng; Yuhong Yin; Ying Li; Lizhen Zhao; Xiaoyan Wu (Elsevier, 2024)
Objective: Monitoring the disease status of Epstein-Barr virus (EBV)-related hemophagocytic lymphohistiocytosis (HLH) patients is crucial. This study aimed to investigate the different strategies and outcomes of patients with EBV-HLH and re-elevated EBV-DNA. Method: A retrospective analysis was conducted on 20 patients diagnosed with EBV-HLH. Clinical features, laboratory tests, treatments, plasma EBV-DNA levels, and outcomes were assessed. Three cases were highlighted for detailed analysis. Results: Nine of the 20 patients had a re-elevation of EBV-DNA during treatment, and 55.5 % (5/9) experienced relapses. Patients with persistently positive plasma EBV-DNA (n = 4) and those with re-elevated EBV-DNA after conversion (n = 9) showed a significantly higher relapse rate compared to those with persistently negative EBV-HLH (n = 7) (p < 0.05). Among the highlighted cases, Case 1 exhibited plasma EBV-DNA re-elevation after four weeks of treatment without relapse, maintaining stability with the original treatment regimen, and eventually, his plasma EBV-DNA turned negative. In Case 2, plasma EBV-DNA was elevated again with a recurrence of HLH after L-DEP. Consequently, she underwent allogeneic hematopoietic stem cell transplantation and eventually achieved complete remission (CR) with negative plasma EBV-DNA. Case 3 experienced plasma EBV-DNA re-elevation after L-DEP but remained in CR, discontinuing chemotherapy without relapse. Conclusion: The re-elevation of plasma EBV-DNA during EBV-HLH treatment poses challenges in determining disease status and treatment strategies. Optimal management decisions require a combination of the level of elevated EBV-DNA, the intensity of hyperinflammation, and the patient's immune function.